The efficacy, safety and tolerability of pantoprazole-based one-week triple therapy in H-pylori eradication and duodenal ulcer healing - (:unkn) unknown (TAYLOR & FRANCIS LTD, 2004)
Objective: Recently, proton pump inhibitor (PPI)-based triple therapy has been recommended as a first line treatment in the eradication of Helicobacter pylori. The aim of this open, multicentre trial was to investigate the efficacy, safety, tolerability and the ulcer healing rate of a triple regimen consisting of pantoprazole(.) 40 mg, clarithromycin 500 mg and amoxicillin 1000 mg twice daily for 7 days, in the eradication of H. pylori in patients with duodenal ulcer in Turkey. Research design and methods: H. pylori infection was assessed by histological examination and rapid urease test at baseline and 4 weeks after the completion of the therapy. Seventy-seven patients were enrolled, 5 were excluded due to various reasons and 72 completed the entire course of the trial. Results: H. pylon eradication was confirmed in 49 of these patients; the eradication rate was 68% by per-protocol analysis and 63.6% by intention-to-treat analysis. The ulcers were completely healed in 61 patients (85%) at the second endoscopic examination. Drug compliance was excellent (97.3%) and there were no serious adverse events. Conclusion: Pantoprazole-based 1-week triple therapy was well tolerated and the ulcer healing rate was high (85%). Relatively low H. pylori eradication rates may be attributed to rising antibiotic resistance over recent years. A large scale, comparative study with other PPI-based regimens is warranted based on the results of this open study with the pantoprazole-based regimen.
Keywords: amoxicillin; clarithromycin; duodenal ulcer; eradication; H. pylori; pantoprazole; ANTIMICROBIAL RESISTANCE; UNITED-STATES; CLARITHROMYCIN; AMOXICILLIN; METRONIDAZOLE; POPULATION; INFECTION; REGIMENS; PATTERN; TURKEY